Panelist Acceptance, Proximate Characteristics of Amino Acids and Volatile Compounds, and Color Profile of Fermented Cempedak (Artocarpus champeden) and Oyster Mushroom (Pleurotus ostreatus) Seasoning - Miftakhur Rohmah; Bernatal Saragih; Nur Amaliah; Rimbawan Apriadi; Anton Rahmadi (Journal of Food Quality)
The potential of mandai cempedak (Artocarpus champeden) powder to be mixed with other abundant raw materials such as oyster mushroom (Pleurotus ostreatus) as a flavoring ingredient is an exciting thing to study as a unique flavor source for the archipelago. This study aims to observe panelist acceptance, proximate characteristics of amino acid, volatile compounds, and color profiles on five mixed formulas of fermented cempedak (Artocarpus champeden) and oyster mushroom (Pleurotus ostreatus) seasoning. The five seasoning formulas combine 30–70% flavored mushroom powder and 30–70% mandai cempedak powder with control of commercial mushroom powder and pure mandai powder. Hedonic quality assessment on seasoning samples of flavored mushroom powder and mandai cempedak powder played a more critical role in the acceptance of the final product, with a slightly reddish yellow color tendency with a paleness level of around 66–67%. Seasoning samples had a savory taste with dominant amino acid profiles of ileusine (1.46%, w/w), glutamate (1.37%), methionine (0.82%), and aspartic acid (0.72%). All seasoning formulations of flavored mushroom and mandai cempedak powder have a moisture content of 8.4–10.9%, total protein 7.0–9.0%, soluble protein 2.4–3.5%, ash content 4.5–19.2%, fat content 2.3–4.5%, carbohydrates 62.7–79.4%, and the solubility is 31.0–89.4%. The dominant volatile compounds in seasoning are heptanone, dodecoxyethanol, and etradecyloxyethanol with pleasant aroma profiles, pungent fruity, green, citrus, and herbal. In conclusion, mandai cempedak powder to be mixed with other abundant raw materials such as oyster mushroom (Pleurotus ostreatus) can be used as a typical Indonesian flavor ingredient with unique characteristics in terms of its amino acid content, volatile compounds, and essential oils.